The Last Glacial Maximum and Deglacial History of the Seno Skyring Ice Lobe (52°S), Southern Patagonia - Lira, María-Paz; García, Juan-Luis; Bentley, Michael J.; Jamieson, Stewart S. R.; Darvill, Christopher M.; Hein, Andrew S.; Fernández, Hans; Rodés, Ángel; Fabel, Derek; Smedley, Rachel K.; Binnie, Steven A. (Frontiers in Earth Science, 2022)
There are still many uncertainties about the climatic forcing that drove the glacier fluctuations of the Patagonian Ice Sheet (PIS, 38-55°S) during the last glacial period. A key source of uncertainty is the asynchrony of ice lobe fluctuations between the northern, central, and southern PIS throughout the last glacial period. To fully understand the regional trends requires careful mapping and extensive geochronological studies. This paper presents geomorphological and geochronological reconstructions of the glacial and deglacial landforms formed during the last glacial period at the Seno Skyring lobe, southernmost Patagonia (52°S, 71°W). We present a detailed geomorphological map, where we identify two moraine systems. The outer and older is named Laguna Blanca (LB) and the inner Río Verde (RV). The LB moraines were built subaerially, whereas parts of the RV were deposited subaqueously under the palaeo lake Laguna Blanca, which developed during deglaciation. We conducted surface exposure 10Be dating methods on boulder samples collected from LB and RV glacial margins. The moraine LB III and LB IV formed at 26.3 ±2.3 ka (n=5) and 24.3 ±0.9 ka (n=3), respectively. For the inner RV moraine, we obtained an age of 18.7 ±1.5 ka (n=6). For the palaeo Laguna Blanca evolution, we performed 10Be exposure ages on shoreline berms and optically stimulated luminesce dating to constrain the lake levels, and 10Be depth profile dating on an outwash deposit formed by a partial lake drainage event, which occurred at 22 ±3 ka. For the RV moraine deglaciation, we performed radiocarbon dating of basal sediments in a peat bog, which indicates that the glacier retreated from the terminal RV moraine by at least c. 16.4 cal kyr BP. Our moraine geochronology shows an asynchrony in the maximum extents and a different pattern of ice advances between neighbouring lobes in southern Patagonia. We speculate that this may be due, at least in part, to the interaction between topography and the precipitation carried by the southern westerly wind belt. However, we found broad synchrony of glacial readvances contemporaneous with the RV moraine.